Calcium and Phosphorus Dynamics in Trichoderma-Fermented Napier grass–Banana Peel Blends - Jusman Jusman; Abdul Latief Fattah (Edupedia Publisher, 2025)
Optimizing nutrient utilization from forage and residue combinations is crucial for advancing sustainable ruminant feeding systems. This study evaluated the dynamics of calcium (Ca) and phosphorus (P) in a mixture of Napier grass (Pennisetum purpureum) and banana peel (Musa acuminata × balbisiana) fermented by Trichoderma at various addition levels. A completely randomized design with four treatments was applied, and mineral concentrations were determined using standard laboratory procedures. Results showed a consistent increase in Ca content with higher banana peel additions, while P levels decreased, indicating a differential mineral response to fermentation. Relative changes showed an enrichment of Ca up to 24.05% and a decrease in P concentration, reflecting fermentation-mediated transformation of the substrate matrix. The Ca:P ratio increased from 1.39 to 1.96 across treatments, remaining within the acceptable nutritional range but approaching Ca-dominant conditions at higher addition levels. These findings indicate that microbial fermentation not only improves feed utilization but also re-establishes the mineral balance in the forage-residue system. Moderate inclusion levels provide a more balanced mineral profile, highlighting the importance of optimizing feed composition. Overall, integrating agro-industrial residues through fermentation offers a viable strategy to improve nutritional efficiency and support sustainable livestock production.